El manejo de inventarios como factor de competitividad para la empresa comercializadora de pinturas automotrices, Autocolores G Ltda. (2020)
Autocolores G Ltda. is the largest national distributor of Axalta Coating Systems, a North American company formerly called Dupont, dedicated to the development, manufacture and sale of liquid and powder coatings for vehicles. The main objective of this work is to determine the inventory management system suitable for the national distribution company Autocolores G Ltda., which will correct the frequent shortages that afflict them. We have carried out a research, observing weaknesses in the processes that take place in the purchasing area due to the lack of definition of these and some processes that do not add value, causing the information that is generated in the center and the distribution points not an adequate treatment is applied. We collect information through the survey technique directed towards the employees of the company, which serves as an orientation to carry out the strategy to mitigate the problem that is currently being presented and that correct the frequent shortage that is afflicting, through a logistical diagnosis that define the system that the company uses at the time, and in this way define purchasing policies, establishing a minimum and maximum order point that generates an optimal flow of inventories.